2008
DOI: 10.1177/0022219408315814
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Serial Naming Is a Unique Predictor of Spelling in Children

Abstract: Some previous research has shown strong associations between spelling ability and rapid automatic naming (RAN) after controls for phonological processing and nonsense-word reading ability, consistent with the double-deficit hypothesis in reading and spelling. Previous studies did not, however, control for nonsense-word spelling ability before assessing RAN--spelling associations. In this study, 65 children with poor spelling skills but average reasoning ability completed RAN tasks and spelling, reading, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
2
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 73 publications
11
83
2
10
Order By: Relevance
“…Beyond the effects of letter knowledge, RAN also predicted unique variance in spelling. The contribution of RAN on spelling in English has been well established (e.g., Bowers et al, 1999;Savage, Pillay, & Melidona, 2008). Bowers and Wolf (1993) have argued that slow naming speed prevents the integration of visual information from the letter sequences of words.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the effects of letter knowledge, RAN also predicted unique variance in spelling. The contribution of RAN on spelling in English has been well established (e.g., Bowers et al, 1999;Savage, Pillay, & Melidona, 2008). Bowers and Wolf (1993) have argued that slow naming speed prevents the integration of visual information from the letter sequences of words.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that reading fluency measures are more closely related to NSDs, whereas reading accuracy measures are related to PDs (Bowers, 1995). In addition, naming speed has been related to spelling (Savage, Pillay, & Melidona, 2008). Therefore, differences between taxa on measures of reading fluency, comprehension and spelling were of interest, in addition to reading-related measures of vocabulary and listening comprehension.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, most of the research on RAN has been conducted in the field of dyslexia and reading research. This research has found evidence of linkages between RAN and various aspects of literacy, including reading accuracy (e.g., Compton, 2000;Cornwall, 1992; Cutting & Denckla, 2001;Kirby, Parrila, & Pfeiffer, 2003;Manis, Seidenberg, & Doi, 1999;Schatschneider et al, 2004; Wolf, 1997Wolf, , 1999, reading fluency (e.g., Torppa, Georgiou, Salmi, Eklund & Lyytinen, 2012;, and reading comprehension (Badian, 1993;Neuhaus, Foorman, Francis, & Carlson, 2001;Schatschneider et al, 2004;Sprugevica & Høien 2003, and also spelling (Georgiou, Torppa, Manolitsis, Lyytinen, & Parrila, 2012;Savage, Pillay, & Melidona, 2008;Torppa et al, 2012;. However, the research evidence thus far has shown the strongest support for a connection between RAN and reading fluency (often defined as speed of accurate response to oral reading tasks) or reading speed, as the evidence on the connections with other aspects of reading or spelling have been more or less conflicting (for reviews, see Georgiou & Parrila, 2013;.…”
mentioning
confidence: 99%